Leadership in Democracy - Brooker, P. author. aut Link
VIII, 217 p.
Keywords: Leadership in Democracy develops and applies an innovative leadership theory of democracy and political evolution, based upon Schumpeter's famous theories of democracy and economic entrepreneurship. The new theory is applied to the US and British democracies in an assessment of how much entrepreneurial-style, pioneering leadership occurred from the 1960s to the 1990s in the electoral, governmental, legislative, administrative and policy-advocacy sectors of democracies. The assessment leads on to a wide-ranging appraisal of the prospects for 'entrepreneurial' democracy in the twenty-first century.